Finite bivariate biorthogonal N - Konhauser polynomials - Lekesiz, E. Guldogan; Cekim, B.; Ozarslan, M. A. (Taylor & Francis Ltd, 2025)
A new set of finite 2D biorthogonal polynomials is defined using the finite orthogonal polynomials $ N_{n}<^>{\left (p\right ) }\left (w\right ) $ Nn(p)(w) and Konhauser polynomials. We present a connection between this finite 2D biorthogonal set and the generalized Laguerre-Konhauser polynomials. Also, we obtain several applications of finite bivariate biorthogonal N - Konhauser polynomials.
Keywords: Biorthogonal polynomial; finite orthogonal polynomial; Konhauser polynomial; partial differential equation; generating function; fractional calculus